Reﬂections on Online EFL Teaching during COVID-19: A Case Study of Yunnan University in China - Wang, Wenjun (Journal of NELTA, 2022)
The paper is a case study on a whole-term online English teaching practice of non-English major postgraduates from March to July 2020 at Yunnan University in China. By attempting to probe into the strategies employed in the three phases of pre-teaching, while-teaching, and post-teaching respectively, reflections upon the mega-scale online English teaching for 30 classes of approximately 1200 students are analyzed by qualitative research in the forms of online interviews and class video observation. The research aims to summarize useful strategies and key factors teachers need to attach importance to in technology-assisted English language teaching with mixed applications and approaches to meet an urgent need in practical situations. Th e practice can be an example of the effective “localization” of college English teaching in China. It also shows that effectiveness-oriented online teaching can be feasible and useful in shaping and enriching the new normal of foreign language teaching in post COVID-19 era.